Pattern forming composition
A triazine ring-containing polymer with a hydroxyl-substituted arylamino group and crosslinking agent forms transparent fine patterns with high refractive index, addressing the challenges of reverse taper shapes and undercuts in negative-tone materials, suitable for electronic devices.
Patent Information
- Application Number
- JP2021563956
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-04-09
- Filing Date
- 2020-12-07
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2040-12-07
AI Technical Summary
Existing negative-tone materials for forming high refractive index patterns in electronic devices suffer from reverse taper shapes and undercuts, making it difficult to produce convex lens-shaped patterns.
A pattern-forming composition containing a triazine ring-containing polymer capped with a hydroxyl-substituted arylamino group and a crosslinking agent, which forms transparent fine patterns with high refractive index and low volume shrinkage.
The composition enables the formation of fine patterns with high heat resistance, high refractive index, and excellent transparency, suitable for applications in electronic devices such as liquid crystal displays, organic electroluminescent displays, and optical semiconductors.
Smart Images

Figure 0007605132000036 
Figure 0007605132000037 
Figure 0007605132000038
Abstract
Description
[Technical field]
[0001] The present invention relates to a pattern-forming composition. [Background technology]
[0002] In recent years, there has been a demand for highly functional polymer materials in the development of electronic devices such as liquid crystal displays, organic electroluminescence (EL) displays, touch panels, optical semiconductor (LED) elements, solid-state imaging elements, organic thin-film solar cells, dye-sensitized solar cells, and organic thin-film transistors (TFTs). Specific properties required include 1) heat resistance, 2) transparency, 3) high refractive index, 4) high solubility, 5) low volumetric shrinkage, 6) high temperature and humidity resistance, and 7) high film hardness. In view of this, the present applicant has already discovered that a polymer containing a repeating unit having a triazine ring and an aromatic ring has a high refractive index, and can achieve high heat resistance, high transparency, high refractive index, high solubility, and low volume shrinkage by itself, and is suitable as a film-forming composition for producing electronic devices (Patent Document 1).
[0003] However, organic electroluminescence displays generally have a problem in that they have low light extraction efficiency, that is, the efficiency with which generated light escapes to the outside of the device. Various technologies have been developed so far as light extraction methods can be used to solve this problem. One known technology is to use a high refractive index layer or pattern to eliminate the difference in refractive index between layers, which is one of the causes of light loss before it is emitted to the outside. For this high refractive index pattern, many negative photosensitive compositions have been proposed, and the present applicant has also reported various materials capable of forming a negative high refractive index pattern (see Patent Documents 2 to 4).
[0004] However, with negative materials, a pattern is formed by leaving behind the parts that have been hardened by the light irradiated from above, so that the shape after development generally tends to be inverted tapered shape and undercuts are likely to occur, making it particularly difficult to produce a pattern in the shape of a so-called convex lens. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] International Publication No. 2010 / 128661 [Patent Document 2] International Publication No. 2016 / 024613 [Patent Document 3] International Publication No. 2016 / 114337 [Patent Document 4] International Publication No. 2019 / 093203 Summary of the Invention [Problem to be solved by the invention]
[0006] Therefore, there is a demand for a composition capable of forming a negative type high refractive index pattern. The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a pattern-forming composition capable of forming a pattern having a high refractive index and excellent transparency. [Means for solving the problem]
[0007] Means for Solving the Problems The present inventors have conducted intensive research in order to achieve the above object, and as a result have found that a transparent fine pattern having a high refractive index can be formed by using a composition containing a triazine ring-containing polymer in which at least a portion of the triazine ring ends are blocked with hydroxyl-substituted arylamino groups, and a crosslinking agent, and have completed the present invention.
[0008] That is, the present invention provides [1] A pattern-forming composition comprising: a triazine ring-containing polymer that includes a repeating unit structure represented by the following formula (1) and has at least one triazine ring terminal, at least a portion of which is terminated with a hydroxyl-substituted arylamino group; a crosslinking agent; and an organic solvent: [ka] In the formula, R and R′ each independently represent a hydrogen atom, an alkyl group, an alkoxy group, an aryl group, or an aralkyl group; Ar 1 represents at least one selected from the group represented by the following formulas (2) to (13). [ka] [In the formula, R 1 ~R 92 each independently represents a hydrogen atom, a halogen atom, a sulfo group, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms; R 93 and R 94 represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, W 1 and W 2 are, independently of each other, a single bond, CR 95 R 96 (R 95 and R 96 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms (which may be joined together to form a ring), C=O, O, S, SO, SO2, or NR 97 (R 97 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a phenyl group; X 1 and X 2 are each independently a single bond, an alkylene group having 1 to 10 carbon atoms, or a group represented by the following formula (14): [ka] (In the formula, R 98 ~R101 each independently represents a hydrogen atom, a halogen atom, a sulfo group, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms; Y 1 and Y 2 each independently represents a single bond or an alkylene group having 1 to 10 carbon atoms. [2]. A composition for pattern formation according to [1], wherein the hydroxyl-substituted arylamino group is represented by the following formula (15): [ka] [3]. A composition for pattern formation according to [2], wherein the hydroxyl-substituted arylamino group is represented by the following formula (16): [ka] [4]. Ar 1 A composition for pattern formation, represented by the following formula (17): [1] to [3] [ka] [5] The pattern-forming composition according to any one of [1] to [4], wherein the crosslinking agent is a polyfunctional (meth)acrylic compound. [6]. A pattern-forming composition according to any one of [1] to [5], which is for use in a light extraction layer of an organic electroluminescence element. [7]. A cured product produced from the pattern-forming composition according to any one of [1] to [5]. [8]. A hardened product of [7] which is a lens. [9] An electronic device comprising a substrate and a cured product according to [7] or [8] formed on the substrate.
[10] . Organic electroluminescence (EL) electronic device [9].
[11] An optical member comprising a substrate and a cured product according to [7] or [8] formed on the substrate.
[12] A method for producing a pattern, comprising applying the pattern-forming composition according to any one of [1] to [5] to a substrate, evaporating the organic solvent, irradiating the substrate with light through a mask on which a pattern has been formed, developing the substrate, and baking the substrate;
[13] A triazine ring-containing polymer comprising a repeating unit structure represented by the following formula (1), having at least one triazine ring terminal, at least a portion of which is terminated with a hydroxyl group-substituted arylamino group: [ka] In the formula, R and R′ each independently represent a hydrogen atom, an alkyl group, an alkoxy group, an aryl group, or an aralkyl group; Ar 1 represents at least one selected from the group represented by the following formulas (2) to (13). [ka] [In the formula, R 1 ~R 92 each independently represents a hydrogen atom, a halogen atom, a sulfo group, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms; R 93 and R 94 represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, W 1 and W 2 are, independently of each other, a single bond, CR 95 R 96 (R 95 and R 96 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms (which may be joined together to form a ring), C=O, O, S, SO, SO2, or NR 97 (R 97 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a phenyl group; X 1 and X 2 are each independently a single bond, an alkylene group having 1 to 10 carbon atoms, or a group represented by the following formula (14): [ka] (In the formula, R 98 ~R 101 each independently represents a hydrogen atom, a halogen atom, a sulfo group, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms; Y 1 and Y 2 each independently represents a single bond or an alkylene group having 1 to 10 carbon atoms.
[14] . The triazine ring-containing polymer of
[13] , wherein the hydroxyl group-substituted arylamino group is represented by the following formula (15): [ka]
[15] . The triazine ring-containing polymer of
[14] , wherein the hydroxyl group-substituted arylamino group is represented by the following formula (16): [ka]
[16] . 1 A triazine ring-containing polymer represented by the following formula (17):
[13] to
[15] [ka] to provide. Effect of the Invention
[0009] The composition of the present invention can be masked or otherwise exposed to light and cured in a pattern, and then developed with an alkali and baked to give a fine pattern with a high refractive index and excellent transparency. A pattern produced from the composition of the present invention can exhibit properties such as high heat resistance, high refractive index, and low volume shrinkage due to the triazine ring-containing polymer, and can therefore be suitably used in the fields of electronic devices and optical materials, such as a part of the materials used in producing liquid crystal displays, organic electroluminescence (EL) displays, touch panels, optical semiconductor (LED) elements, solid-state imaging elements, organic thin-film solar cells, dye-sensitized solar cells, organic thin-film transistors (TFTs), lenses, prisms, cameras, binoculars, microscopes, semiconductor exposure devices, etc. In particular, a pattern formed from the composition of the present invention can be suitably used as a pattern-forming product for extracting light from an organic EL display. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a 1H-NMR spectrum of the polymer compound [4] obtained in Example 1. [Diagram 2] FIG. 1 is a 1H-NMR spectrum of the polymer compound [5] obtained in Example 2. [Diagram 3] 1 is an optical microscope photograph of the patterned film produced in Example 3. [Figure 4] 1 is an electron microscope photograph of a patterned film produced in Example 3. [Diagram 5] 1 is an optical microscope photograph of the patterned film produced in Example 4. [Figure 6] 1 is an electron microscope photograph of the patterned film produced in Example 4. [Figure 7] 1 is an optical microscope photograph of the patterned film produced in Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in further detail below. The pattern-forming composition according to the present invention is characterized in that it comprises a triazine ring-containing polymer which includes a repeating unit structure represented by the following formula (1) and has at least one triazine ring terminal, at least a portion of which is terminated with a hydroxyl-substituted arylamino group, a crosslinker, and an organic solvent.
[0012] (1) Triazine ring-containing polymer The triazine ring-containing polymer used in the present invention contains a repeating unit structure represented by the following formula (1). The triazine ring-containing polymer is, for example, a so-called hyperbranched polymer. A hyperbranched polymer is a highly branched polymer having an irregular branching structure. Here, the irregularity means that the branching structure is more irregular than that of a dendrimer, which is a highly branched polymer having a regular branching structure. For example, a triazine ring-containing polymer that is a hyperbranched polymer contains a structure (structure A) that is larger than the repeating unit structure represented by formula (1) and is formed by bonding the repeating unit structure represented by formula (1) to each of three bonds of the repeating unit structure represented by formula (1). In the triazine ring-containing polymer that is a hyperbranched polymer, structure A is distributed throughout the entire triazine ring-containing polymer except for the terminals. In the triazine ring-containing polymer which is a hyperbranched polymer, the repeating unit structure may essentially consist of only the repeating unit structure represented by formula (1).
[0013] [ka]
[0014] In the above formula, R and R' each independently represent a hydrogen atom, an alkyl group, an alkoxy group, an aryl group, or an aralkyl group, but from the viewpoint of further increasing the refractive index, it is preferable that both are hydrogen atoms. In the present invention, the number of carbon atoms in the alkyl group is not particularly limited, but is preferably 1 to 20, and in consideration of further improving the heat resistance of the polymer, the number of carbon atoms in the alkyl group is more preferably 1 to 10, and even more preferably 1 to 3. In addition, the structure of the alkyl group is not particularly limited, and may be, for example, any of linear, branched, cyclic, and combinations of two or more of these.
[0015] Specific examples of alkyl groups include methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, s-butyl, t-butyl, cyclobutyl, 1-methyl-cyclopropyl, 2-methyl-cyclopropyl, n-pentyl, 1-methyl-n-butyl, 2-methyl-n-butyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, 1,2-dimethyl-n-propyl, 2,2-dimethyl-n-propyl, 1-ethyl-n-propyl, cyclopentyl, 1-methyl-cyclobutyl, 2-methyl-cyclobutyl, 3-Methyl-cyclobutyl, 1,2-dimethyl-cyclopropyl, 2,3-dimethyl-cyclopropyl, 1-ethyl-cyclopropyl, 2-ethyl-cyclopropyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl-n-butyl, 2,2-dimethyl-n-butyl, 2,3-dimethyl-n-butyl, 3,3-dimethyl-n-butyl, 1-ethyl-n-butyl, 2-ethyl- n-Butyl, 1,1,2-trimethyl-n-propyl, 1,2,2-trimethyl-n-propyl, 1-ethyl-1-methyl-n-propyl, 1-ethyl-2-methyl-n-propyl, cyclohexyl, 1-methyl-cyclopentyl, 2-methyl-cyclopentyl, 3-methyl-cyclopentyl, 1-ethyl-cyclobutyl, 2-ethyl-cyclobutyl, 3-ethyl-cyclobutyl, 1,2-dimethyl-cyclobutyl, 1,3-dimethyl-cyclobutyl, 2,2-dimethyl-cyclobutyl, 2,3-dimethyl-cyclobutyl, 2,4-dimethyl Examples of such cyclopropyl ether include ethyl-cyclobutyl, 3,3-dimethyl-cyclobutyl, 1-n-propyl-cyclopropyl, 2-n-propyl-cyclopropyl, 1-isopropyl-cyclopropyl, 2-isopropyl-cyclopropyl, 1,2,2-trimethyl-cyclopropyl, 1,2,3-trimethyl-cyclopropyl, 2,2,3-trimethyl-cyclopropyl, 1-ethyl-2-methyl-cyclopropyl, 2-ethyl-1-methyl-cyclopropyl, 2-ethyl-2-methyl-cyclopropyl, and 2-ethyl-3-methyl-cyclopropyl groups.
[0016] The number of carbon atoms in the alkoxy group is not particularly limited, but is preferably 1 to 20, and in consideration of further improving the heat resistance of the polymer, the number of carbon atoms in the alkoxy group is more preferably 1 to 10, and even more preferably 1 to 3. In addition, the structure of the alkyl portion is not particularly limited, and may be, for example, any of linear, branched, cyclic, and combinations of two or more of these.
[0017] Specific examples of alkoxy groups include methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, s-butoxy, t-butoxy, n-pentoxy, 1-methyl-n-butoxy, 2-methyl-n-butoxy, 3-methyl-n-butoxy, 1,1-dimethyl-n-propoxy, 1,2-dimethyl-n-propoxy, 2,2-dimethyl-n-propoxy, 1-ethyl-n-propoxy, n-hexyloxy, 1-methyl-n-pentyloxy, 2-methyl-n-pentyloxy, 3-methyl-n-pentyloxy, and 2-methyl-n-pentyloxy. Examples of the aryloxy group include pentyloxy, 4-methyl-n-pentyloxy, 1,1-dimethyl-n-butoxy, 1,2-dimethyl-n-butoxy, 1,3-dimethyl-n-butoxy, 2,2-dimethyl-n-butoxy, 2,3-dimethyl-n-butoxy, 3,3-dimethyl-n-butoxy, 1-ethyl-n-butoxy, 2-ethyl-n-butoxy, 1,1,2-trimethyl-n-propoxy, 1,2,2-trimethyl-n-propoxy, 1-ethyl-1-methyl-n-propoxy, and 1-ethyl-2-methyl-n-propoxy groups.
[0018] The number of carbon atoms in the aryl group is not particularly limited, but is preferably 6 to 40. In order to further improve the heat resistance of the polymer, the number of carbon atoms is more preferably 6 to 16, and even more preferably 6 to 13. In the present invention, the aryl group includes an aryl group having a substituent, such as a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a nitro group, and a cyano group. Specific examples of the aryl group include phenyl, o-chlorophenyl, m-chlorophenyl, p-chlorophenyl, o-fluorophenyl, p-fluorophenyl, o-methoxyphenyl, p-methoxyphenyl, p-nitrophenyl, p-cyanophenyl, α-naphthyl, β-naphthyl, o-biphenylyl, m-biphenylyl, p-biphenylyl, 1-anthryl, 2-anthryl, 9-anthryl, 1-phenanthryl, 2-phenanthryl, 3-phenanthryl, 4-phenanthryl, and 9-phenanthryl groups.
[0019] The number of carbon atoms in the aralkyl group is not particularly limited, but is preferably 7 to 20. The structure of the alkyl portion is not particularly limited, and may be, for example, linear, branched, cyclic, or a combination of two or more of these. In the present invention, the aralkyl group includes an aralkyl group having a substituent, for example, a halogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, a nitro group, a cyano group, and the like. Specific examples thereof include benzyl, p-methylphenylmethyl, m-methylphenylmethyl, o-ethylphenylmethyl, m-ethylphenylmethyl, p-ethylphenylmethyl, 2-propylphenylmethyl, 4-isopropylphenylmethyl, 4-isobutylphenylmethyl, and α-naphthylmethyl groups.
[0020] The above Ar 1 represents at least one selected from the group represented by formulas (2) to (13).
[0021] [ka]
[0022] Above R 1 ~R 92 each independently represents a hydrogen atom, a halogen atom, a sulfo group, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms; R 93 and R94 represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, W 1 and W 2 are, independently of each other, a single bond, CR 95 R 96 (R 95 and R 96 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms (which may be joined together to form a ring), C=O, O, S, SO, SO2, or NR 97 (R 97 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a phenyl group. Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. The alkyl group and alkoxy group include the same as those mentioned above. Also, X 1 and X 2 each independently represents a single bond, an alkylene group having 1 to 10 carbon atoms, or a group represented by the formula (14). The structures of these alkyl groups, alkoxy groups, and alkylene groups are not particularly limited, and may be, for example, linear, branched, cyclic, or a combination of two or more of these.
[0023] [ka]
[0024] Above R 98 ~R 101 each independently represents a hydrogen atom, a halogen atom, a sulfo group, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms; Y 1 and Y 2 each independently represents a single bond or an alkylene group having 1 to 10 carbon atoms. As the halogen atom, the alkyl group, and the alkoxy group, R 1 ~R 92 Examples of the halogen atom, alkyl group and alkoxy group are the same as those in the above. R 98 ~R 101 The structures of the alkyl group and alkoxy group in the formula (I) are not particularly limited, and may be, for example, linear, branched, cyclic, or a combination of two or more of these. Y 1 and Y 2 The structure of the alkylene group in is not particularly limited and may be, for example, any of linear, branched, cyclic, and combinations of two or more thereof. Examples of the alkylene group having 1 to 10 carbon atoms include methylene, ethylene, propylene, trimethylene, tetramethylene, and pentamethylene groups. The structure of the alkylene group is not particularly limited, and may be, for example, any of linear, branched, cyclic, and combinations of two or more of these.
[0025] In particular, Ar 1 As the aryl group, at least one of the groups represented by the formulae (2), (5) to (13) is preferable, and at least one of the groups represented by the formulae (2), (5), (7), (8), and (11) to (13) is more preferable. Specific examples of the aryl group represented by the formulae (2) to (13) above include, but are not limited to, those represented by the following formulae:
[0026] [ka] "Ph" represents a phenyl group.
[0027] Among these, aryl groups represented by the following formula are more preferred because they give polymers with higher refractive indexes.
[0028] [ka]
[0029] In particular, in order to further increase the solubility of the triazine ring-containing polymer in a highly safe solvent such as a resist solvent, Ar 1 is preferably an m-phenylene group represented by the formula (17).
[0030] [ka]
[0031] In the triazine ring-containing polymer used in the present invention, at least a part of the triazine ring terminals is blocked with a hydroxyl-substituted arylamino group in order to improve the solubility of a thin film or cured film obtained by using the polymer in an alkaline developer. The hydroxyl group is a hydroxyl group directly bonded to an aryl group, i.e., a so-called phenolic hydroxyl group. The aryl group may be the same as those exemplified above, with a phenyl group being particularly preferred. The number of hydroxyl groups on the aryl group is not particularly limited, but in consideration of the balance between developability in an alkaline developer and solubility in organic solvents, one hydroxyl group is preferred. From these viewpoints, in the present invention, as the hydroxyl-substituted arylamino group, a hydroxyl-substituted phenylamino group represented by formula (15) is preferred, and a phenylamino group having a hydroxyl group at the meta position of the amino group represented by formula (16) is more preferred.
[0032] [ka]
[0033] [ka]
[0034] The weight average molecular weight of the triazine ring-containing polymer in the present invention is not particularly limited, but is preferably 500 to 500,000, more preferably 500 to 100,000. From the viewpoint of further improving heat resistance and reducing shrinkage, it is preferably 2,000 or more. From the viewpoint of further increasing solubility and reducing the viscosity of the obtained solution, it is preferably 50,000 or less, more preferably 30,000 or less, even more preferably 15,000 or less, and still more preferably 10,000 or less. The weight average molecular weight in the present invention is an average molecular weight obtained by gel permeation chromatography (hereinafter, referred to as GPC) analysis in terms of standard polystyrene.
[0035] The triazine ring-containing polymer (hyperbranched polymer) of the present invention can be produced in accordance with the method disclosed in the above-mentioned WO 2010 / 128661. For example, as shown in the following scheme 1, a triazine ring-containing polymer (19) can be obtained by reacting a triazine compound (18) with an aryldiamino compound (20) in a suitable organic solvent.
[0036] [ka] (In the formula, X's each independently represent a halogen atom.)
[0037] In the above reaction, the charging ratio of the aryldiamino compound (20) is arbitrary as long as the target polymer is obtained, but the charging ratio is preferably 0.01 to 10 equivalents, more preferably 0.7 to 5 equivalents, of the diamino compound (20) relative to 1 equivalent of the triazine compound (18). The aryldiamino compound (20) may be added neat or in the form of a solution dissolved in an organic solvent. In view of ease of operation and control of the reaction, the latter method is preferred. The reaction temperature may be appropriately set within the range from the melting point of the solvent used to the boiling point of the solvent, and is preferably about -30 to 150°C, more preferably -10 to 100°C.
[0038] As the organic solvent, various solvents commonly used in this type of reaction can be used, for example, tetrahydrofuran, dioxane, dimethyl sulfoxide; amide solvents such as N,N-dimethylformamide, N-methyl-2-pyrrolidone, tetramethylurea, hexamethylphosphoramide, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide, N-methyl-2-piperidone, N,N-dimethylethyleneurea, N,N,N',N'-tetramethylmalonic acid amide, N-methylcaprolactam, N-acetylpyrrolidine, N,N-diethylacetamide, N-ethyl-2-pyrrolidone, N,N-dimethylpropionic acid amide, N,N-dimethylisobutylamide, N-methylformamide, and N,N'-dimethylpropyleneurea, and mixed solvents thereof. Among these, N,N-dimethylformamide, dimethyl sulfoxide, N-methyl-2-pyrrolidone, N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide and mixtures thereof are preferred, and N,N-dimethylacetamide, 3-methoxy-N,N-dimethylpropanamide, 3-butoxy-N,N-dimethylpropanamide and N-methyl-2-pyrrolidone are particularly suitable.
[0039] In the reaction of the above scheme 1, various bases that are commonly used may be added during or after the polymerization. Specific examples of the base include potassium carbonate, potassium hydroxide, sodium carbonate, sodium hydroxide, sodium bicarbonate, sodium ethoxide, sodium acetate, lithium carbonate, lithium hydroxide, lithium oxide, potassium acetate, magnesium oxide, calcium oxide, barium hydroxide, trilithium phosphate, trisodium phosphate, tripotassium phosphate, cesium fluoride, aluminum oxide, ammonia, n-propylamine, trimethylamine, triethylamine, diisopropylamine, diisopropylethylamine, N-methylpiperidine, 2,2,6,6-tetramethyl-N-methylpiperidine, pyridine, 4-dimethylaminopyridine, N-methylmorpholine, 2-aminoethanol, ethyldiethanolamine, diethylaminoethanol, and the like. The amount of the base to be added is preferably 1 to 100 equivalents relative to 1 equivalent of the triazine compound (18), and more preferably 1 to 10 equivalents. These bases may be used in the form of an aqueous solution. It is preferred that no raw material components remain in the resulting polymer, but some raw materials may remain as long as the effects of the present invention are not impaired. After completion of the reaction, the product can be easily purified by a method such as reprecipitation.
[0040] As described above, the triazine ring-containing polymer of the present invention has at least one triazine ring terminal, and at least a portion of the triazine ring terminal is blocked with a hydroxyl group-substituted arylamino group. As the method for terminal blocking, a known method may be adopted. For example, the triazine ring-containing polymer (19) obtained by the above method may be treated with an arylamine compound having a phenolic hydroxyl group, such as aminophenol, which is an end blocking agent that provides an end blocking group. In this case, the amount of the end-capping agent used is preferably about 0.05 to 10 equivalents, more preferably 0.1 to 5 equivalents, and even more preferably 0.5 to 2 equivalents, per equivalent of halogen atoms derived from the excess triazine compound not used in the polymerization reaction. The reaction solvent and reaction temperature may be the same as those described in Scheme 1 above. The end-capping agent may be charged simultaneously with the aryldiamino compound (20). In addition to the hydroxyl-substituted arylamine compound, an arylamine compound having no substituent may be used to cap the ends with two or more types of groups.
[0041] In the present invention, particularly suitable triazine ring-containing polymers include those represented by the formulae (21) to (24), but are not limited thereto.
[0042] [ka] (Wherein, R, R', and R 1 ~R 4 has the same meaning as above.)
[0043] [ka] (In the formula, R 1 ~R 4 has the same meaning as above.)
[0044] [ka]
[0045] [ka]
[0046] (2) Crosslinking agent The crosslinking agent used in the present invention is not particularly limited as long as it is a compound that can undergo a crosslinking reaction alone or together with the above-mentioned triazine ring-containing polymer to form a crosslinked structure. Examples of such compounds include melamine-based compounds having a crosslinking substituent such as a methylol group or a methoxymethyl group (e.g., a phenoplast compound, an aminoplast compound, etc.), a substituted urea-based compound, a compound containing a crosslinking substituent such as an epoxy group or an oxetane group (e.g., a polyfunctional epoxy compound, a polyfunctional oxetane compound, etc.), a compound containing a blocked isocyanate group, a compound having an acid anhydride group, a compound having a (meth)acrylic group, etc., from the viewpoint of heat resistance and storage stability, a compound containing an epoxy group, a blocked isocyanate group, or a (meth)acrylic group is preferred, and in particular, a compound having a blocked isocyanate group, or a polyfunctional epoxy compound and / or a polyfunctional (meth)acrylic compound that gives a composition that can be photocured without using an initiator is preferred. When these compounds are used for crosslinking between polymers or when they form a crosslinked structure by themselves, they must have at least two crosslink-forming substituents.
[0047] The polyfunctional epoxy compound is not particularly limited as long as it has two or more epoxy groups in one molecule. Specific examples thereof include tris(2,3-epoxypropyl)isocyanurate, 1,4-butanediol diglycidyl ether, 1,2-epoxy-4-(epoxyethyl)cyclohexane, glycerol triglycidyl ether, diethylene glycol diglycidyl ether, 2,6-diglycidylphenyl glycidyl ether, 1,1,3-tris[p-(2,3-epoxypropoxy)phenyl]propane, 1,2-cyclohexanedicarboxylic acid diglycidyl ester, 4,4'-methylenebis(N,N-diglycidylaniline), 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, trimethylolethane triglycidyl ether, bisphenol-A diglycidyl ether, and pentaerythritol polyglycidyl ether.
[0048] Commercially available products include epoxy resins having at least two epoxy groups, YH-434 and YH434L (manufactured by Nippon Steel Chemical & Material Co., Ltd.); epoxy resins having a cyclohexene oxide structure, Epolead GT-401, GT-403, GT-301, GT-302, Celloxide 2021, and 3000 (manufactured by Daicel Corporation); bisphenol A type epoxy resins, jER1001, 1002, 1003, 1004, 1007, 1009, 1010, and 828 (all manufactured by Mitsubishi Chemical Co., Ltd.); and bisphenol F type epoxy resins. jER807 (manufactured by Mitsubishi Chemical Corporation), phenol novolac type epoxy resins jER152 and jER154 (both manufactured by Mitsubishi Chemical Corporation), EPPN201 and EPPN202 (both manufactured by Nippon Kayaku Co., Ltd.), cresol novolac type epoxy resins EOCN-102, EOCN-103S, EOCN-104S, EOCN-1020, EOCN-1025, and EOCN-1027 (both manufactured by Nippon Kayaku Co., Ltd.), jER180S75 (manufactured by Mitsubishi Chemical Corporation), alicyclic epoxy resins Denacol EX-252 (manufactured by Nagase ChemteX Corporation), CY175, CY177, and CY179 (all manufactured by CIBA-GEIGY Co., Ltd.), AG), Araldite CY-182, CY-192, and CY-184 (all manufactured by CIBA-GEIGY AG), Epiclon 200 and 400 (all manufactured by DIC Corporation), jER871 and jER872 (all manufactured by Mitsubishi Chemical Corporation), ED-5661 and ED-5662 (all manufactured by Celanese Coatings Co., Ltd.), and aliphatic polyglycidyl ethers such as Denacol EX-611, EX-612, EX-614, EX-622, EX-411, EX-512, EX-522, EX-421, EX-313, EX-314, and EX-321 (manufactured by Nagase ChemteX Corporation) can also be used.
[0049] The polyfunctional (meth)acrylic compound is not particularly limited as long as it has two or more (meth)acrylic groups in one molecule. Specific examples thereof include ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, ethoxylated bisphenol A diacrylate, ethoxylated bisphenol A dimethacrylate, ethoxylated trimethylolpropane triacrylate, ethoxylated trimethylolpropane trimethacrylate, ethoxylated glycerin triacrylate, ethoxylated glycerin trimethacrylate, ethoxylated pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetramethacrylate, ethoxylated dipentaerythritol hexaacrylate, polyglycerin monoethylene oxide, and the like. Examples of the polyacrylate include side polyacrylate, polyglycerin polyethylene glycol polyacrylate, dipentaerythritol hexaacrylate, dipentaerythritol hexamethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, and polybasic acid-modified acrylic oligomers.
[0050] In addition, the polyfunctional (meth)acrylic compound is commercially available. Specific examples thereof include NK Ester A-200, A-400, A-600, A-1000, A-9300 (tris(2-acryloyloxyethyl)isocyanurate), A-9300-1CL, A-TMPT, UA-53H, 1G, 2G, 3G, 4G, 9G, 14G, 23G, ABE-300, A-BPE-4, A-BPE-6, A-BPE-10, A-BPE-20, and A-BPE-3. 0, BPE-80N, BPE-100N, BPE-200, BPE-500, BPE-900, BPE-1300N, A-GLY-3E, A-GLY-9E, A-GLY-20E, A-TMPT-3EO, A-TMPT-9EO, AT-20E, ATM-4E, ATM-35E, A-DPH, A-TMPT, A-DCP, A-HD-N, TMPT, DCP, NPG, HD-N, A-DPH-12E, A-DPH-48E, A-DPH-96E, NK Oligo U-15HA, NK PolymerVanarasin GH-1203 (manufactured by Shin-Nakamura Chemical Co., Ltd.), KAYARAD (registered trademark) DPHA, NPGDA, PET30, DPEA-12, PEG400DA, THE-330, RP-1040, DN-0075 (manufactured by Nippon Kayaku Co., Ltd.), Aronix M-210, Aronix M-303, Aronix M-305, Aronix M-306, Aronix M-309, Aronix M-306, Aronix M-310, Aronix M-31 3. M-315, M-321, M-350, M-360, M-400, M-402, M-403, M-404, M -405, M-406, M-408, M-450, M-452, M-460 (manufactured by Toagosei Co., Ltd.), DPGDA, HDDA, TPGDA, HPNDA, PETIA, PETRA, TMPTA, TMPEOTA, EBECRYL11, 40, 13 5, 140, 145, 150, 180, 1142, 204, 205, 210, 215, 220, 230, 2 44, 245, 265, 270, 280 / 15IB, 284, 294 / 25HD, 303, 436, 438, 4 46, 450, 524, 525, 600, 605, 645, 648, 767, 770, 800, 810, 811, 812, 846, 851, 852, 853, 860, 884, 885, 1259, 1290, 1606, 1830, 1870, 3500, 3603, 3608, 3700, 3701, 3702, 3703, 3708, 4820, 4858, 5129, 6040, 8210, 8454, 8301R, 8307, 8311, 84 02, 8405, 8411, 8465, 8701, 8800, 8804, 8807, 9270, 9227EA, 936, KRM8200, 8200AE, 7735, 8296, 08452, 8904, 8528, 8912, OTA480, IRR214-K, 616, 679, 742, 793, PEG400DA-D(ACA)Z200M, Z230AA, Z250, Z251, Z300, Z320, and Z254F (all manufactured by Daicel-Allnex Co., Ltd.). The polybasic acid-modified acrylic oligomer is also available as a commercial product, and specific examples thereof include Aronix M-510 and 520 (both manufactured by Toagosei Co., Ltd.).
[0051] The compound having an acid anhydride group is not particularly limited as long as it is a carboxylic acid anhydride obtained by dehydration condensation of two molecules of carboxylic acid, and specific examples thereof include compounds having one acid anhydride group in the molecule, such as phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, nadic anhydride, methylnadic anhydride, maleic anhydride, succinic anhydride, octyl succinic anhydride, and dodecenyl succinic anhydride; 1,2,3,4-cyclobutanetetracarboxylic dianhydride, pyromellitic anhydride, and 3,4-dicarboxy-1,2,3,4-tetrahydro-1-naphthalene. Examples of the dianhydride include succinic dianhydride, bicyclo[3.3.0]octane-2,4,6,8-tetracarboxylic dianhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, 1,2,3,4-butanetetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride, and 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, which have two acid anhydride groups in the molecule.
[0052] The compound containing a blocked isocyanate group is not particularly limited as long as it has two or more blocked isocyanate groups in one molecule, in which the isocyanate group (-NCO) is blocked with an appropriate protecting group, and when exposed to high temperatures during heat curing, the protecting group (blocking moiety) is thermally dissociated and removed, and the resulting isocyanate group undergoes a urethane bond reaction with the phenolic hydroxyl group of the triazine ring-containing polymer of the present invention. For example, a compound having two or more groups represented by the following formula in one molecule (note that these groups may be the same or different from each other) may be mentioned.
[0053] [ka] (In the formula, R b represents an organic group in the block portion.)
[0054] Such a compound can be obtained, for example, by reacting a compound having two or more isocyanate groups in one molecule with a suitable blocking agent. Examples of compounds having two or more isocyanate groups in one molecule include polyisocyanates such as isophorone diisocyanate, 1,6-hexamethylene diisocyanate, methylene bis(4-cyclohexyl isocyanate), and trimethylhexamethylene diisocyanate, as well as dimers and trimers thereof, and reaction products of these with diols, triols, diamines, or triamines. Examples of blocking agents include alcohols such as methanol, ethanol, isopropanol, n-butanol, 2-ethoxyhexanol, 2-N,N-dimethylaminoethanol, 2-ethoxyethanol, and cyclohexanol; phenols such as phenol, o-nitrophenol, p-chlorophenol, and o-, m-, or p-cresol; lactams such as ε-caprolactam, oximes such as acetone oxime, methyl ethyl ketone oxime, methyl isobutyl ketone oxime, cyclohexanone oxime, acetophenone oxime, and benzophenone oxime; pyrazoles such as pyrazole, 3,5-dimethylpyrazole, and 3-methylpyrazole; and thiols such as dodecanethiol and benzenethiol.
[0055] Compounds containing a blocked isocyanate group are also available as commercially available products. Specific examples thereof include Takenate (registered trademark) B-830, B-815N, B-842N, B-870N, B-874N, B-882N, B-7005, B-7030, B-7075, and B-5010 (all manufactured by Mitsui Chemicals, Inc.), Duranate (registered trademark) 17B-60PX, TPA-B80E, MF-B60X, MF-K60X, and E402-B80T (all manufactured by Asahi Kasei Corporation), Karenz MOI-BM (registered trademark) (all manufactured by Showa Denko K.K.), and TRIXENE (registered trademark). Examples include BI7950, 7951, 7960, 7961, 7982, 7990, 7991, and 7992 (all manufactured by Baxenden Chemical Co.).
[0056] The aminoplast compound is not particularly limited as long as it has two or more methoxymethyl groups in one molecule, and examples thereof include melamine compounds such as the Cymel series, such as hexamethoxymethylmelamine CYMEL (registered trademark) 303, tetrabutoxymethylglycoluril 1170, and tetramethoxymethylbenzoguanamine 1123 (all manufactured by Nihon Cytec Industries Co., Ltd.), and the Nikalac series, such as methylated melamine resins Nikalac (registered trademark) MW-30HM, MW-390, MW-100LM, and MX-750LM, and methylated urea resins MX-270, MX-280, and MX-290 (all manufactured by Sanwa Chemical Co., Ltd.). The polyfunctional oxetane compound is not particularly limited as long as it has two or more oxetanyl groups in one molecule, and examples thereof include OXT-221, OX-SQ-H, and OX-SC (all manufactured by Toagosei Co., Ltd.), which contain oxetanyl groups.
[0057] The phenoplast compound has two or more hydroxymethyl groups in one molecule, and when exposed to high temperatures during heat curing, a crosslinking reaction proceeds through a dehydration condensation reaction between the phenolic hydroxyl groups of the triazine ring-containing polymer of the present invention. Examples of phenoplast compounds include 2,6-dihydroxymethyl-4-methylphenol, 2,4-dihydroxymethyl-6-methylphenol, bis(2-hydroxy-3-hydroxymethyl-5-methylphenyl)methane, bis(4-hydroxy-3-hydroxymethyl-5-methylphenyl)methane, 2,2-bis(4-hydroxy-3,5-dihydroxymethylphenyl)propane, bis(3-formyl-4-hydroxyphenyl)methane, bis(4-hydroxy-2,5-dimethylphenyl)formylmethane, and α,α-bis(4-hydroxy-2,5-dimethylphenyl)-4-formyltoluene. Phenoplast compounds are also available as commercially available products, and specific examples include 26DMPC, 46DMOC, DM-BIPC-F, DM-BIOC-F, TM-BIP-A, BISA-F, BI25X-DF, and BI25X-TPA (all manufactured by Asahi Organic Chemicals Co., Ltd.).
[0058] Among these, polyfunctional (meth)acrylic compounds are preferred because they can suppress the decrease in refractive index caused by the incorporation of a crosslinking agent and because the curing reaction proceeds quickly. Among these, dipentaerythritol hexaacrylate and its EO adduct are preferred from the viewpoint of controlling the shape of fine patterns. Examples of such polyfunctional (meth)acrylic compounds include NK Ester A-DPH and NK Ester A-DPH-12E (both manufactured by Shin-Nakamura Chemical Co., Ltd.).
[0059] The above-mentioned crosslinking agent may be used alone or in combination of two or more. The amount of the crosslinking agent used is preferably 1 to 200 parts by mass relative to 100 parts by mass of the triazine ring-containing polymer, but considering the solvent resistance, the lower limit is preferably 2 parts by mass, more preferably 5 parts by mass, and further, considering the control of the refractive index and the residue of the unexposed part, the upper limit is preferably 150 parts by mass, more preferably 100 parts by mass, and even more preferably 90 parts by mass.
[0060] (3) Initiator The composition of the present invention can also contain an initiator according to each crosslinking agent. As described above, when a polyfunctional epoxy compound and / or a polyfunctional (meth)acrylic compound is used as a crosslinking agent, photocuring proceeds without the use of an initiator to give a cured film, but in this case, an initiator may be used.
[0061] When a polyfunctional epoxy compound is used as a crosslinking agent, a photoacid generator or a photobase generator can be used. The photoacid generator may be appropriately selected from known ones and used. For example, onium salt derivatives such as diazonium salts, sulfonium salts and iodonium salts can be used. Specific examples thereof include aryl diazonium salts such as phenyl diazonium hexafluorophosphate, 4-methoxyphenyl diazonium hexafluoroantimonate, and 4-methylphenyl diazonium hexafluorophosphate; diaryliodonium salts such as diphenyl iodonium hexafluoroantimonate, di(4-methylphenyl)iodonium hexafluorophosphate, and di(4-tert-butylphenyl)iodonium hexafluorophosphate; triphenylsulfonium hexafluoroantimonate, tris(4-methoxyphenyl)sulfonium hexafluorophosphate, diphenyl-4-thiophenoxyphenylsulfonium hexafluoroantimonate, and diphenyl-4-thiophenoxyphenylsulfonium hexafluorophosphate. triarylsulfonium salts such as 4,4'-bis(diphenylsulfonio)phenylsulfide-bishexafluoroantimonate, 4,4'-bis(diphenylsulfonio)phenylsulfide-bishexafluorophosphate, 4,4'-bis[di(β-hydroxyethoxy)phenylsulfonio]phenylsulfide-bishexafluoroantimonate, 4,4'-bis[di(β-hydroxyethoxy)phenylsulfonio]phenylsulfide-bis-hexafluorophosphate, 4-[4'-(benzoyl)phenylthio]phenyl-di(4-fluorophenyl)sulfonium hexafluoroantimonate, and 4-[4'-(benzoyl)phenylthio]phenyl-di(4-fluorophenyl)sulfonium hexafluorophosphate.
[0062] These onium salts may be commercially available products, and specific examples thereof include San-Aid SI-60, SI-80, SI-100, SI-60L, SI-80L, SI-100L, SI-L145, SI-L150, SI-L160, SI-L110, and SI-L147 (all manufactured by Sanshin Chemical Industry Co., Ltd.), UVI-6950, UVI-6970, UVI-6974, UVI-6990, and UVI-6992 (all manufactured by Union Carbide Corporation), CPI-100P, CPI-100A, CPI-200K, and CPI-200S (all manufactured by San-Apro Co., Ltd.), Adeka Optomer SP-150, SP-151, SP-170, and SP-171 (all manufactured by Asahi Denka Kogyo Co., Ltd.), and Irgacure. 261 (BASF), CI-2481, CI-2624, CI-2639, CI-2064 (all manufactured by Nippon Soda Co., Ltd.), CD-1010, CD-1011, CD-1012 (all manufactured by Sartomer), DS-100, DS-101, DAM-101, DAM-102, DAM-105, DAM-201, DSM-301, NAI-100, NAI-101, NAI-105, NAI-106, SI-100, SI-101, SI-105, SI-106, PI-105, NDI-105, BENZOIN Examples of such binders include TOSYLATE, MBZ-101, MBZ-301, PYR-100, PYR-200, DNB-101, NB-101, NB-201, BBI-101, BBI-102, BBI-103, BBI-109 (all manufactured by Midori Chemical Co., Ltd.), PCI-061T, PCI-062T, PCI-020T, PCI-022T (all manufactured by Nippon Kayaku Co., Ltd.), IBPF, IBCF (manufactured by Sanwa Chemical Co., Ltd.), and the like.
[0063] On the other hand, the photobase generator may be appropriately selected from known ones, and for example, Co-amine complex-based, oxime carboxylate-based, carbamate-based, and quaternary ammonium salt-based photobase generators may be used. Specific examples thereof include 2-nitrobenzylcyclohexylcarbamate, triphenylmethanol, O-carbamoylhydroxylamide, O-carbamoyloxime, [[(2,6-dinitrobenzyl)oxy]carbonyl]cyclohexylamine, bis[[(2-nitrobenzyl)oxy]carbonyl]hexane 1,6-diamine, 4-(methylthiobenzoyl)-1-methyl-1-morpholinoethane, (4-morpholinobenzoyl)-1-benzyl-1-dimethyla amminecobalt(III) tris(triphenylmethylborate), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone, 2,6-dimethyl-3,5-diacetyl-4-(2'-nitrophenyl)-1,4-dihydropyridine, 2,6-dimethyl-3,5-diacetyl-4-(2',4'-dinitrophenyl)-1,4-dihydropyridine, and the like. Moreover, the photobase generator may be a commercially available product, specific examples of which include TPS-OH, NBC-101, and ANC-101 (all product names, manufactured by Midori Kagaku Co., Ltd.).
[0064] When a photoacid or base generator is used, it is preferably used in the range of 0.1 to 15 parts by mass, more preferably 1 to 10 parts by mass, per 100 parts by mass of the polyfunctional epoxy compound. If necessary, an epoxy resin curing agent may be added in an amount of 1 to 100 parts by mass based on 100 parts by mass of the polyfunctional epoxy compound.
[0065] On the other hand, when a polyfunctional (meth)acrylic compound is used, a photoradical polymerization initiator can be used. The photoradical polymerization initiator may be appropriately selected from known initiators, and examples thereof include acetophenones, benzophenones, Michler's benzoyl benzoate, amyloxime esters, oxime esters, tetramethylthiuram monosulfide, and thioxanthones. In particular, photocleavage type photoradical polymerization initiators are preferred. Photocleavage type photoradical polymerization initiators are described in Latest UV Curing Technology (page 159, publisher: Takasuki Kazuhiro, publisher: Technical Information Association Co., Ltd., published in 1991). Examples of commercially available photoradical polymerization initiators include BASF's trade names: Irgacure 127, 184, 369, 379, 379EG, 651, 500, 754, 819, 903, 907, 784, 2959, CGI1700, CGI1750, CGI1850, CG24-61, OXE01, OXE02, OXE03, OXE04, Darocur 1116, 1173, MBF, BASF's trade name: Lucirin TPO, UCB's trade name: Ubecryl P36, Fratelli Lamberti's trade name: Ezacure KIP150, KIP65LT, KIP100F, KT37, KT55, KTO46, KIP75 / B, and the like. When a photoradical polymerization initiator is used, it is preferably used in the range of 0.1 to 200 parts by mass, and more preferably 1 to 150 parts by mass, per 100 parts by mass of the polyfunctional (meth)acrylate compound.
[0066] (4) Organic Solvent Specific examples of organic solvents include toluene, p-xylene, o-xylene, m-xylene, ethylbenzene, styrene, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, ethylene glycol monoisopropyl ether, ethylene glycol methyl ether acetate, propylene glycol monomethyl ether acetate, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, propylene glycol monobutyl ether, ethylene glycol monobutyl ether, diethylene glycol diethyl ether, dipropylene glycol monomethyl ether, diethylene glycol monomethyl ether, dipropylene glycol monoethyl ether, diethylene glycol monoethyl ether, triethylene glycol dimethyl ether, diethylene glycol monoethyl ether acetate, diethylene glycol, 1-octanol, ethylene glycol, hexylene glycol, , trimethylene glycol, 1-methoxy-2-butanol, cyclohexanol, diacetone alcohol, furfuryl alcohol, tetrahydrofurfuryl alcohol, propylene glycol, benzyl alcohol, 1,3-butanediol, 1,4-butanediol, 2,3-butanediol, γ-butyrolactone, acetone, methyl ethyl ketone, methyl isopropyl ketone, diethyl ketone, methyl isobutyl ketone, methyl normal butyl ketone, cyclopentanone, cyclohexanone, ethyl acetate, isopropyl acetate, normal propyl acetate propyl, isobutyl acetate, normal butyl acetate, ethyl lactate, methanol, ethanol, isopropanol, tert-butanol, allyl alcohol, normal propanol, 2-methyl-2-butanol, isobutanol, normal butanol, 2-methyl-1-butanol, 1-pentanol, 2-methyl-1-pentanol, 2-ethylhexanol, 1-methoxy-2-propanol, tetrahydrofuran, 1,4-dioxane, N,N-dimethylformamide, N,N-dimethylacetamide (DMAc), N-methylpyrrolidone, 1,Examples of the dimethyl ether include 3-dimethyl-2-imidazolidinone, dimethyl sulfoxide, and N-cyclohexyl-2-pyrrolidinone. These may be used alone or in combination of two or more.
[0067] In this case, the solid content concentration in the composition is not particularly limited as long as it is within a range that does not affect storage stability, and may be appropriately set according to the intended thickness of the film. Specifically, from the viewpoints of solubility and storage stability, the solid content concentration is preferably 0.1 to 50 mass%, more preferably 0.1 to 40 mass%.
[0068] (5) Other additives The composition of the present invention may contain other components other than the triazine ring-containing polymer, crosslinking agent and solvent, such as additives such as a leveling agent, a surfactant, a silane coupling agent, a polymerization inhibitor, an antioxidant, a rust inhibitor, a release agent, a plasticizer, an antifoaming agent, a thickener, a dispersant, an antistatic agent, an antisettling agent, a pigment, a dye, an ultraviolet absorber, a light stabilizer and inorganic fine particles, so long as the effects of the present invention are not impaired. Examples of the surfactant include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene stearyl ether, polyoxyethylene cetyl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkyl aryl ethers such as polyoxyethylene octylphenol ether and polyoxyethylene nonylphenol ether; polyoxyethylene-polyoxypropylene block copolymers; sorbitan fatty acid esters such as sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, sorbitan monooleate, sorbitan trioleate, and sorbitan tristearate; and nonionic surfactants such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan trioleate, and polyoxyethylene sorbitan tristearate. 01, EF303, EF352 (manufactured by Mitsubishi Materials Electronics Co., Ltd. (formerly JEMCO Co., Ltd.)), product name Megafac F171, F173, R-08, R-30, R-40, R-41, F-114, F-410, F-430, F-444, F-477, F-552, F-553, F-554, F-555, F-556, F-557, F-558, F-559, F-561, F-562, F-563, RS-75, RS-72-K, RS-76-E, RS-76NS, RS-77 (manufactured by DIC Co., Ltd.), Fluorad FC4 Fluorine-based surfactants such as FC30, FC431 (manufactured by Sumitomo 3M Limited), Asahi Guard AG710, Surflon S-382, SC101, SC102, SC103, SC104, SC105, and SC106 (manufactured by AGC Corporation), organosiloxane polymer KP341 (manufactured by Shin-Etsu Chemical Co., Ltd.), BYK-302, BYK-307, BYK-322, BYK-323, BYK-330, BYK-333, BYK-370, BYK-375, and BYK-378 (manufactured by BYK Japan KK), and the like.
[0069] These surfactants may be used alone or in combination of two or more. The amount of the surfactant used is preferably 0.0001 to 5 parts by mass, more preferably 0.001 to 1 part by mass, and even more preferably 0.01 to 0.5 parts by mass, based on 100 parts by mass of the triazine ring-containing polymer.
[0070] (6) Pattern making method and cured product In the method for producing a pattern using the composition of the present invention, the composition is applied to a substrate, and then heated as necessary to evaporate the solvent, and then heated or irradiated with light to form a desired cured film. When producing a cured film by light irradiation, the composition is irradiated with light through a mask on which a desired pattern is formed, and then developed with a developer to form a fine pattern. In addition, a cured product can be obtained by using the pattern-forming composition of the present invention. The cured product is, for example, a fine pattern (lens) in the shape of a convex lens. In another example of the method for forming a pattern, instead of irradiating light through a mask on which a desired pattern is formed, pattern-wise light irradiation using a laser may be performed. In this case, any method for applying the composition may be used, and for example, methods such as spin coating, dipping, flow coating, inkjet coating, jet dispenser coating, spraying, bar coating, gravure coating, slit coating, roll coating, transfer printing, brush coating, blade coating, and air knife coating may be used.
[0071] Examples of the substrate include substrates made of silicon, glass coated with indium tin oxide (ITO), glass coated with indium zinc oxide (IZO), polyethylene terephthalate (PET), plastic, glass, quartz, ceramics, etc., and flexible substrates having flexibility can also be used. The baking temperature is not particularly limited as long as it is for the purpose of evaporating the solvent, and the baking can be performed at, for example, 70 to 400°C. The baking time may be any time required for the solvent to evaporate, and may be, for example, 1 to 600 seconds. The baking method is not particularly limited, and may be, for example, evaporation using a hot plate or oven in a suitable atmosphere such as air, an inert gas such as nitrogen, or a vacuum. The baking temperature and baking time may be selected according to the process steps of the target electronic device, and baking conditions may be selected such that the physical properties of the resulting film meet the required characteristics of the electronic device. The conditions for light irradiation are not particularly limited, and appropriate irradiation energy and time may be selected depending on the triazine ring-containing polymer and crosslinking agent used.
[0072] Development after exposure can be carried out, for example, by immersing the exposed resin in an organic solvent developer or an aqueous developer. Specific examples of organic solvent developers include PGME (propylene glycol monomethyl ether), PGMEA (propylene glycol monomethyl ether acetate), a mixed solvent of PGME and PGMEA, NMP (N-methyl-2-pyrrolidone), γ-butyrolactone, DMSO (dimethyl sulfoxide), etc., while specific examples of aqueous developers include alkaline aqueous solutions such as sodium carbonate, potassium carbonate, sodium hydroxide, potassium hydroxide, and tetramethylammonium hydroxide.
[0073] The composition of the present invention is baked after the development, whereby the pattern reflows to obtain a fine pattern (lens) having a desired convex lens shape. The lens has a high refractive index and excellent transparency. Therefore, the composition of the present invention is suitable as a lens forming composition. In this case, the firing temperature is not particularly limited, but is preferably 70 to 400°C, more preferably 80 to 200°C, and even more preferably 85 to 150°C. The baking time is also optional, but taking into consideration that the desired lens shape is obtained by reflow, it is preferably 1 to 60 minutes, more preferably 5 to 35 minutes, and even more preferably 7 to 15 minutes. The firing method can be the same as that described above.
[0074] The composition of the present invention may further contain an oxirane ring-containing compound and a photocurable catalyst. The oxirane ring-containing compound may be one having one or more, preferably two or more, oxirane rings in the molecule, and specific examples thereof include glycidyl ether type epoxy resins, glycidyl ester type epoxy resins, alicyclic epoxy resins, epoxy-modified polybutadiene resins, oxetane compounds, etc. These may be used alone or in combination of two or more. The amount of the oxirane ring-containing compound to be blended is not particularly limited, but can be about 10 to 400 parts by mass per 100 parts by mass of the triazine ring-containing polymer.
[0075] The photocurable catalyst may be a photocation generator. Specific examples of the photocation generator include triarylsulfonium salts such as triphenylsulfonium hexafluorophosphate and triphenylsulfonium hexafluoroantimonate; triarylselenium salts; diaryliodonium salts such as diphenyliodonium hexafluorophosphate and diphenyliodonium hexafluoroantimonate. These may be used alone or in combination of two or more. The amount of the photocuring catalyst is not particularly limited, but can be about 0.1 to 100 parts by mass with respect to 100 parts by mass of the triazine ring-containing polymer.
[0076] The oxirane ring-containing compound and the photocurable catalyst may be mixed in any order with the other components constituting the composition of the present invention, and the organic solvent described above may be used in the blend. The composition containing these is also applied by the above-mentioned method, and then, for example, ultraviolet light or the like is irradiated at 1 to 4000 mJ / cm 2 The light irradiation may be carried out by using various known methods such as a high pressure mercury lamp, a metal halide lamp, a xenon lamp, an LED, or a laser beam. If necessary, the film may be heated at about 85 to 150° C. before or after exposure. Development after exposure can be carried out by immersing the exposed resin in the above-mentioned organic solvent developer or aqueous developer.
[0077] The size of the lens of the present invention is not particularly limited as long as it can be used as a high refractive index pattern of an organic EL element, but the width is preferably 0.1 to 1,000 μm, more preferably 0.5 to 500 μm, and even more preferably 1 to 100 μm, and the height is preferably 0.1 to 100 μm, more preferably 0.5 to 50 μm, and even more preferably 1 to 25 μm.
[0078] The lens of the present invention obtained as described above can achieve high heat resistance, a high refractive index, and low volume shrinkage, and can therefore be suitably used in the fields of electronic devices and optical materials, such as as a part of the materials used in the production of liquid crystal displays, organic electroluminescence (EL) displays, touch panels, optical semiconductor (LED) elements, solid-state imaging elements, organic thin-film solar cells, dye-sensitized solar cells, organic thin-film transistors (TFTs), lenses, prism cameras, binoculars, microscopes, semiconductor exposure devices, and the like. In particular, the lens of the present invention has a convex lens shape, is highly transparent, and has a high refractive index, and therefore can be suitably used in applications that require a high refractive index pattern, such as light extraction applications and black matrix applications for organic EL displays. EXAMPLES
[0079] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples. The measuring devices used in the examples are as follows. [ 1 H-NMR] Equipment: Bruker NMR System AVANCE III HD 500(500MHz) Measurement solvent: DMSO-d6 Reference material: tetramethylsilane (TMS) (δ 0.0 ppm) [GPC] Apparatus: Tosoh Corporation HLC-8200 GPC Column: Tosoh TSKgel α-3000 + Tosoh TSKgel α-4000 Column temperature: 40℃ Solvent: dimethylformamide (DMF) Detector: UV (271 nm) Calibration curve: Standard polystyrene [Ellipsometer] Equipment: J.A. Woollam Japan Multi-angle Spectroscopic Ellipsometer VASE [Spectrophotometer] Equipment: Konica Minolta CM-3700A [Turbidity meter] Equipment: HAZE METER NDH 5000 manufactured by Nippon Denshoku Industries Co., Ltd. [Optical microscope] Equipment: OLYMPUS BX51 manufactured by Olympus Optical Co., Ltd. [Electron microscope] Equipment: JEOL JSM-7400F [exposure] Equipment: SUSS Mask Aligner MA6 [developing] Equipment: Actes Kyosan Co., Ltd. small developing device ADE-3000S
[0080] [1] Synthesis of triazine ring-containing polymers [Example 1] Synthesis of polymer compound [4] [ka]
[0081] In a 5,000 mL four-neck flask, 1,3-phenylenediamine [2] (228.70 g, 2.115 mol, Amino-Chem) and 3464.72 g of dimethylacetamide (DMAc, Kanto Chemical Co., Ltd.) were added, and after nitrogen replacement, 1,3-phenylenediamine [2] was dissolved in DMAc by stirring. Then, it was cooled to -10 ° C in an ethanol-dry ice bath, and 2,4,6-trichloro-1,3,5-triazine [1] (390.00 g, 2.115 mol, Tokyo Chemical Industry Co., Ltd.) was added while making sure that the internal temperature did not exceed 0 ° C. After stirring for 30 minutes, the reaction vessel was transferred to an oil bath set at 110-150 ° C, and the reaction solution was heated until the internal temperature reached 85 ° C ± 5 ° C. After stirring for 1 hour, 3-aminophenol [3] (276.95 g, 2.538 mol, manufactured by Tokyo Chemical Industry Co., Ltd.) dissolved in DMAc 649.64 g (manufactured by Kanto Chemical Co., Ltd.) was added dropwise and stirred for 3 hours. Then, 2-aminoethanol (387.53 g, manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise, and after stirring for 30 minutes, the stirring was stopped. Tetrahydrofuran (THF, 2,246 g), ammonium acetate (2,526 g) and ion-exchanged water (2,526 g) were added to the reaction solution and stirred for 30 minutes. After stirring was stopped, the solution was transferred to a separatory funnel, separated into an organic layer and an aqueous layer, and the organic layer was collected. The collected organic layer was added dropwise to a mixture of methanol (8,421 g) and ion-exchanged water (5,614 g) to cause reprecipitation. The resulting precipitate was filtered and dried in a vacuum dryer at 120° C. for 8 hours to obtain 536.2 g of the target polymer compound [4] (hereinafter referred to as P-1). The weight average molecular weight Mw of compound P-1 measured by GPC in terms of polystyrene was 5,970, and the polydispersity Mw / Mn was 2.5. 1 The results of H-NMR spectrum measurement are shown in FIG.
[0082] (1) Solubility check The obtained compound P-1 (3.0 g) was dissolved in propylene glycol monomethyl ether (hereinafter abbreviated as PGME) (7.0 g) and cyclopentanone (hereinafter abbreviated as CPN) (7.0 g), respectively. The compound P-1 was dissolved in both solvents, and a uniform varnish of 30 mass % was obtained. (2) Check the refractive index The obtained compound P-1 (0.749 g), 0.007 g of a 10 mass% PGME solution of Megafac R-40 (manufactured by DIC Corporation) as a surfactant, and 4.243 g of CPN were added to prepare a 15 mass% uniform and transparent film-forming composition (varnish) (hereinafter referred to as P-1 solution). The obtained P-1 solution was spin-coated on a non-alkali glass substrate of 50 mm × 50 mm × 0.7t (0.7 mm) using a spin coater aiming for 1000 nm, pre-baked on a hot plate at 100 ° C for 1 minute, and then baked at 250 ° C for 5 minutes to obtain a cured film (hereinafter referred to as P-1 film) (film thickness 929 nm). The refractive index of the produced cured film at a wavelength of 550 nm was measured and found to be 1.778.
[0083] [Example 2] Synthesis of polymer compound [5] [ka]
[0084] In a 1,000 mL four-neck flask, 1,3-phenylenediamine [2] (45.15 g, 0.418 mol, manufactured by Amino-Chem Co., Ltd.) and 685.16 g of dimethylacetamide (DMAc, manufactured by Kanto Chemical Co., Ltd.) were added, and after replacing with nitrogen, 1,3-phenylenediamine [2] was dissolved in DMAc by stirring. Then, it was cooled to -10 ° C in an ethanol-dry ice bath, and 2,4,6-trichloro-1,3,5-triazine [1] (70.00 g, 0.380 mol, manufactured by Tokyo Chemical Industry Co., Ltd.) was added while making sure that the internal temperature did not exceed 0 ° C. After stirring for 30 minutes, the reaction vessel was transferred to an oil bath set at 90-110 ° C, and the reaction solution was heated until the internal temperature reached 85 ° C ± 5 ° C. After stirring for 1 hour, 3-aminophenol [3] (49.71 g, 0.456 mol, manufactured by Tokyo Chemical Industry Co., Ltd.) dissolved in DMAc 120.91 g (manufactured by Kanto Chemical Co., Ltd.) was added dropwise and stirred for 3 hours. Then, 2-aminoethanol (69.56 g, manufactured by Tokyo Chemical Industry Co., Ltd.) was added dropwise, and after stirring for 30 minutes, the stirring was stopped. Tetrahydrofuran (THF, 416 g), ammonium acetate (468.2 g) and ion-exchanged water (468.2 g) were added to the reaction solution and stirred for 30 minutes. After stirring was stopped, the solution was transferred to a separatory funnel, separated into an organic layer and an aqueous layer, and the organic layer was collected. The collected organic layer was added dropwise to a mixture of methanol (1,040 g) and ion-exchanged water (1,561 g) to cause reprecipitation. The resulting precipitate was filtered and dried in a vacuum dryer at 120°C for 8 hours to obtain 95.1 g of the target polymer compound [5] (hereinafter referred to as P-2). The weight average molecular weight Mw of compound P-2 measured by GPC in terms of polystyrene was 12,384, and the polydispersity Mw / Mn was 3.3. 1 The results of H-NMR spectrum measurement are shown in FIG.
[0085] [2] Preparation of lens-forming composition and production of lenses [Example 3] Compound P-1 (11.731 g) obtained in Example 1, 13.197 g of A-DPH-12E (manufactured by Shin-Nakamura Chemical Co., Ltd.) in an 80 mass% CPN solution as a crosslinker, 3.519 g of OXE-04 (manufactured by BASF) in a 10 mass% CPN solution as a photoradical generator, 0.235 g of Megafac R-40 (manufactured by DIC Corporation) in a 10 mass% CPN solution as a surfactant, and CPN (30.65 g) were mixed and confirmed to be dissolved visually, and a varnish with a solid content of 38.2 mass% was prepared (hereinafter referred to as SP-1 solution).
[0086] (1) Confirmation of the physical properties of the cured film This SP-1 solution was spin-coated onto a 50 mm x 50 mm x 0.7 mm alkali-free glass substrate using a spin coater at 200 rpm for 5 seconds and at 590 rpm for 30 seconds, and then pre-dried at 100°C for 1 minute using a hot plate to obtain a cured film (hereinafter referred to as SP-1 film). The refractive index, thickness, and b * The transmittance from 400 to 800 nm and haze were measured. The results are shown in Table 1. The transmittance was calculated as the average transmittance from 400 to 800 nm.
[0087] [Table 1]
[0088] These results demonstrate that the cured film obtained from the SP-1 solution has the excellent effect of maintaining a high refractive index and a high transmittance even when the film is thick.
[0089] (2) Lens fabrication The SP-1 solution prepared in Example 3 was spin-coated on a non-alkali glass substrate measuring 50 mm × 50 mm × 0.7 mm using a spin coater at 200 rpm for 5 seconds and at 590 rpm for 30 seconds, and the substrate was pre-dried at 100°C for 1 minute using a hot plate. Then, using a mask aligner MA6 manufactured by SUSS, a mask having circular openings with a diameter of 15 μm arranged at 15 μm intervals and spaces (ultraviolet ray shielding areas) corresponding to the remaining areas other than the openings was placed on the coating film, and the substrate was exposed to light with a wavelength of 365 nm at 150 mJ / cm. 2 The exposure dose was 100 μg / ml. After UV irradiation, the substrate was developed with a 2.38% tetramethylammonium hydroxide (TMAH) solution for 40 seconds, and then rinsed with ultrapure water for 30 seconds. After rinsing, the substrate was dried at 100°C for 10 minutes using a hot plate to obtain a patterned film. Optical and electron microscope photographs of the resulting patterned film are shown in FIGS.
[0090] [Example 4] The SP-1 solution prepared in Example 3 was spin-coated on a non-alkali glass substrate measuring 50 mm × 50 mm × 0.7 mm using a spin coater at 200 rpm for 5 seconds and at 590 rpm for 30 seconds, and the substrate was pre-dried at 100°C for 1 minute using a hot plate. Then, using a mask aligner MA6 manufactured by SUSS, a mask having circular openings with a diameter of 15 μm arranged at 15 μm intervals and spaces (ultraviolet ray shielding areas) corresponding to the remaining areas other than the openings was placed on the coating film, and the substrate was exposed to light with a wavelength of 365 nm at 150 mJ / cm. 2 The exposure dose was 100 μg / ml. After UV irradiation, the film was developed using a 2.38% TMAH solution for 40 seconds, and then rinsed with ultrapure water for 30 seconds to obtain a patterned film. Optical and electron microscope photographs of the resulting patterned film are shown in FIGS.
[0091] As shown in Figure 4, the patterned film that was developed and then baked has a convex lens shape, whereas as shown in Figure 6, the patterned film that was not developed and then baked does not have an inverse tapered shape like a normal negative pattern, and although no undercuts are observed, it does not have a convex lens shape. Usually, negative materials harden in the areas where light hits them from above, resulting in an inverse tapered shape, but because the lens shape is the inverse of that, it is difficult to form. However, with the patterning film of Example 3, despite being negative, the pattern reflows when baked after development, resulting in the desired convex lens shape. In this way, it can be said that the present invention has demonstrated an unexpected effect with the normally unlikely combination of negative and reflow.
[0092] [Example 5] The SP-1 solution prepared in Example 3 was spin-coated on a non-alkali glass substrate of 50 mm × 50 mm × 0.7 mm using a spin coater at 200 rpm for 5 seconds and at 930 rpm for 30 seconds, and then pre-dried at 100°C for 1 minute using a hot plate. Then, a mask having a 15 μm-wide linear opening and a 15 μm-wide linear space (ultraviolet shielding portion), called a line & space, was placed on the coating film using a SUSS mask aligner MA6, and the substrate was exposed to 150 mJ / cm 2 of light with a wavelength of 365 nm. 2 The exposure dose was 100 μg / ml. After UV irradiation, the film was developed using a 2.38% TMAH solution for 60 seconds, and then rinsed with ultrapure water for 30 seconds to obtain a patterned film. An optical microscope photograph of the resulting patterned film is shown in FIG.
[0093] As shown in FIG. 7, it can be seen that the present invention can form not only dot-shaped patterns but also line-shaped patterns.
Claims
1. A pattern-forming composition for producing a convex lens-shaped pattern, comprising: a triazine ring-containing polymer that contains a repeating unit structure represented by the following formula (1) and has at least one triazine ring end, at least a portion of which is terminated with a hydroxyl group-substituted arylamino group; a crosslinking agent; and an organic solvent. 【Chemistry 1】 In the formula, R and R′ each independently represent a hydrogen atom, an alkyl group, an alkoxy group, an aryl group, or an aralkyl group; Ar 1 represents at least one selected from the group represented by the following formulas (2) to (13). 【Chemistry 2】 [In the formula, R 1 ~R 92 each independently represents a hydrogen atom, a halogen atom, a sulfo group, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms; R 93 and R 94 represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, W 1 and W. 2 are each independently a single bond, CR 95 R 96 (R 95 and R 96 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms (which may be joined together to form a ring). ), C=O, O, S, SO, SO 2 , or N.R. 97 (R 97 represents a hydrogen atom, an alkyl group having 1 to 10 carbon atoms, or a phenyl group; X 1 and X 2 are each independently a single bond, an alkylene group having 1 to 10 carbon atoms, or a group represented by the following formula (14): 【Chemistry 3】 (In the formula, R 98 ~R 101 each independently represents a hydrogen atom, a halogen atom, a sulfo group, an alkyl group having 1 to 10 carbon atoms, or an alkoxy group having 1 to 10 carbon atoms; Y 1 and Y 2 each independently represents a single bond or an alkylene group having 1 to 10 carbon atoms.
2. 2. The composition for pattern formation according to claim 1, wherein the hydroxyl-substituted arylamino group is represented by the following formula (15): 【Chemistry 4】
3. 3. The composition for pattern formation according to claim 2, wherein the hydroxyl-substituted arylamino group is represented by the following formula (16): 【Chemistry 5】
4. The Ar 1 The composition for pattern formation according to any one of claims 1 to 3, wherein is represented by the following formula (17): 【Chemistry 6】
5. 5. The pattern-forming composition according to claim 1, wherein the crosslinking agent is a polyfunctional (meth)acrylic compound.
6. The pattern-forming composition according to any one of claims 1 to 5, which is used for a light-extraction layer of an organic electroluminescence device.
7. A cured product produced from the pattern-forming composition according to any one of claims 1 to 5, which is a lens having a convex lens shape.
8. An electronic device comprising a substrate and the cured product according to claim 7 formed on the substrate.
9. 9. The electronic device of claim 8 which is an organic electroluminescent device.
10. An optical member comprising a substrate and the cured product according to claim 7 formed on the substrate.
11. A method for producing a pattern, comprising the steps of: applying the pattern-forming composition according to any one of claims 1 to 5 onto a substrate; evaporating the organic solvent; irradiating the substrate with light through a mask on which a pattern has been formed; developing the substrate; and baking the substrate to produce a convex lens-shaped pattern, which is a cured product produced from the pattern-forming composition.
Citation Information
Patent Citations
Triazine dihalide containing phenolic hydroxy group, aromatic (POLY)guanamine and their composition
JP2004156001A
Triazine ring-containing polymer and film-forming composition comprising same
WO2010128661A1
Aromatic polyamide and film-forming composition containing same
WO2014003092A1
Triazine-ring-containing polymer and composition including same
WO2015098787A1
Polymer containing triazine ring and composition containing same
WO2016024613A1
